Cutaneous leishmaniasis in the patients refered to medical laboratories in Mashhad, Iran - Mohhammed Karimian Shirazi; Gholamreza Razmi; Abolghasem Naghibi (Gonabad University of Medical Sciences, 2015)
Cutaneous leishmaniasis is an important parasitic disease in tropical and subtropical areas . There are many nidus in different areas of Iran, such as Khorasan Razavi Province The first step to control of each disease is to determine of risk factors. The aim of study was to study the different epidemiological aspects of cutaneous leishmaniasis. A cross- sectional study was done on persons that were introduced to laboratory to detecte leishmania spp in cutaneous wounds during winter to autumn in 2011- 2012. First, the data in each person was recorded in history form. Then, tissue smear was prepared from cutaneous wound and stained with giemsa methods, after that examined with light microscope with oel lenz. The data of one hunderd peitaint were analysed with statistical methods.: A total of one hundred patients,the frequency male and female were 58% and 42% , respectively (P>0.05). The highest frequency were observed in the age groups of 20-29 year old (34%) and 0-9 year old (24%) (P<0.05). The largest number of cutaneous leishmaniasis was reported in autumn (40%) and the lowest in spring (15%). Eighteen percent of pateints were directly contacted with dogs in house and housework. A total of 217 counted wounds , the majority of wounds were found in hand and face and minority in leg (P<0.05) . The most pateint had one and two wounds and lowest paitent six wound . The diameter of the most wounds were 1-5 mm. The most patients, the wound was appeared less than 6 months before diagnosing. In the present study, The frequency of dried and wet wounds were 76% and 34% , respectively. Based on the results, the frequency of cutaneous of leishmaniasis was high in Mashhad area and need to more surveillance by public health authorities in order to control and prophylaxis of disease